KNOWLEDGE, ATTITUDE, AND HEALTHCARE-SEEKING BEHAVIOR AMONG FAMILIES OF CHILDREN WITH TUBERCULOSIS - Muhammad Reza Saputra; Windy Rakhmawati; Sri Hendrawati; Fanny Adistie (Belitung Raya Foundation, Indonesia, 2020)
Background: Poor family healthcare-seeking behavior may cause delays in pediatric tuberculosis management. Knowledge and attitude are among the basic factors that influence in the family healthcare-seeking behavior. Objective: This study aimed to explore the knowledge, attitude, and healthcare-seeking behavior among families of children with tuberculosis. Methods: This was a cross-sectional descriptive quantitative study using accidental sampling method. Eighty-three families of children with tuberculosis were recruited. World Health Organization's Knowledge, Attitude and Practice Survey guideline was used to develop the questionnaires used in this study. Data were analyzed using descriptive statistics. Results: Results showed that 51.8% of the families had good knowledge and 53% had a positive attitude while 74.7% of the families did not do early screening, 67.5% preferred hospital for examinations, and 51.8% directly visited a health care facility when the child showed signs and symptoms of tuberculosis. In these families, 77.1% delayed taking the child for treatment for < 1 month, and the reason for the delay in 100% of these families was because they did not know that their children had signs and symptoms of tuberculosis. Conclusion: In conclusion, more than half of the families in this study already had good knowledge, attitude, and practice in accessing healthcare services although poor screening practice was still seen in most families. Thus, nurses have opportunities to provide appropriate health-related education to achieve the desired behavioral change.